Fly away - MacLachlan, Patricia (Margaret K. McElderry Books, 2014)
While in North Dakota helping her Aunt Frankie prepare for a possible flood, Lucy finds her voice as a poet with the help of her two-year-old brother Teddy, the rest of their family, and a few cows.